Populações tradicionais e inclusão social no Brasil:Um paralelo entre as políticas de acesso à terra e à educação superior por indígenas e quilombolas - Ana Lúcia Aguiar Melo; José Luiz de Moura Filho (Les Cahiers ALHIM)
The land has always been an asset targeted by capital, and education has become more and more commodified, with the presence, even, of international conglomerates in the Brazilian system. In order to tackle the social inequalities that have deepened during decades of liberal governments, ethnic movements have been demanding the construction of public policies that, although they seek common objectives, deal with the segments according to their specificities. Thus, federal legislation on land regularization provides for different procedures for quilombos remnants and for indigenous peoples, while for access to and permanence in higher education, the regulatory norm deals with the subject in a Universalist way practically identical, under the form of Affirmative Actions, without considering that, in the case of quilombolas, measures are aimed at social inclusion, while in the case of indigenous people, it is an original right. In this way, the present article aims to analyze the trajectory of these two public policies in the territory of the municipality of Santa Maria (Rio Grande do Sul), in which there is not only the Universidade Federal de Santa Maria (UFSM) but also two villages, two indigenous camps and a remaining quilombo community.